Procedural performance is linked to motor skills and language ability: Findings from a knot-tying task in children with and without developmental coordination disorder - Yu-Ting Tseng; Hsinjen Julie Hsu (Acta Psychologica)
Previous studies have demonstrated poor procedural learning of motor sequences in children with developmental coordination disorder (DCD). These studies have largely relied on the serial reaction time paradigm, and results have not always been conclusive. This study examined procedural learning and its association with motor coordination and language ability in children with DCD and typically developing (TD) children, using an ecologically valid knot-tying task. Knot-tying performances, motor skills and language ability were assessed in children with DCD and age- and sex-matched TD children. The DCD group showed longer completion times, lower accuracy, and more error steps than TD peers (all p's < .05). Both completion time and accuracy were significantly correlated with motor skills (manual dexterity and balance) and language ability, with stronger associations observed within the DCD group. These findings extend prior research by demonstrating procedural learning deficits in a functionally relevant, real-world task. The observed associations between knot-tying performances and both motor skills and language ability in the DCD group underscore the need for comprehensive assessments and future studies investigating potential underlying mechanisms linking procedural learning, motor skills, and language development in children with DCD.